Comprehensive phytochemicals analysis and anti‐myocardial ischemia activity of total saponins of American ginseng berry. Issue 2 (3rd January 2022) - Li, Le; Liu, Yunhe; Yu, Hui; Li, Zhuo; Lin, Hongqiang; Wu, Fulin; Tan, Luying; Wang, Caixia; Li, Pingya; Liu, Jinping
Abstract: American ginseng berry (AGB) is a new medicinal source. Total saponins of American ginseng berry (TSAGB) are the main active ingredients. The effects and active saponins of TSAGB on myocardial ischemia (MI) rats were evaluated for the first time. First, there were 69 saponins identified or tentatively characterized by Ultra‐high performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry (UPLC‐Q/TOF‐MS/MS) combined with UNIFI platform, among which, about 28 saponins were first identified in AGB. Second, MI model was established by ligating left coronary artery. It has been demonstrated that TSAGB could prevent the ST‐segment elevation, reduce myocardial infarct size and levels of aspartate aminotransferase (AST), creatine kinase (CK), lactate dehydrogenase (LDH), malondialdehyde (MDA), and elevate the superoxide dismutase (SOD) level. Finally, network pharmacology combined with molecular docking to screen out four active saponins (ginsenoside Re, Rb3, Rg3, and PF11 ) and five key targets (SOD1, LDHA, CKB, GOT2, and ROS1) closely related to MI. Practical applications: This study enriches the chemical composition of TSAGB, and provides a basis for clarifying the pharmacological substances for anti‐myocardial ischemia. TSAGB might be a potential anti‐myocardial ischemia agent. The effect might be related to alleviating oxidative stress. Abstract : The present study clarified the saponin composition of total saponins of American ginseng berry (TSAGB), confirmed its anti‐myocardial ischemia (MI) effect, and screened out four MI‐related active saponins.